Primary Hepatoid Adenocarcinoma of the Lung: A Study of Two Cases with Review of Literature (Indian Journal of Medical and Paediatric Oncology, 2020)
Primary hepatoid adenocarcinoma (HAC) is a rare extrahepatic adenocarcinoma with morphological and phenotypical resemblance to hepatocellular carcinoma (HCC). It can occur in lung, stomach, gallbladder, pancreas, ovary, and uterus, with most common site being stomach. Morphological features of primary HAC of the lung are similar to HCC, so exclusion of metastatic HCC is necessary. In this report, we describe two cases of elderly men with primary pulmonary HAC who presented in advanced clinical stage and diagnosed by fine-needle aspiration cytology with immunohistochemistry. Both patients succumbed to death despite starting first cycle of chemotherapy.
Keywords: Cell block; fine-needle aspiration cytology; hepatoid adenocarcinoma; immunohistochemistry; lung